2010
DOI: 10.1021/es903917f
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Discharge Electrode for Minimizing Ozone Emission from Indoor Corona Devices

Abstract: Ground-level ozone emitted from indoor corona devices poses serious health risks to the human respiratory system and the lung function. Federal regulations call for effective techniques to minimize the indoor ozone production. In this work, stable atmospheric corona discharges from nanomaterials are demonstrated using horizontally suspended carbon nanotubes (CNTs) as the discharge electrode. Compared with the conventional discharges employing micro- or macroscale electrodes, the corona discharge from CNTs coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…When the positive voltage was applied to the graphene‐decorated IWCS, the corona current did not increase, and the corona discharge occurred with difficulty. This was because the graphene surface had hydroxyl, carboxyl, and other functional groups, which was negative charged, making it easy to absorb positive ions . The positive corona discharge current was about two orders of magnitude lower than the negative corona discharge current.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the positive voltage was applied to the graphene‐decorated IWCS, the corona current did not increase, and the corona discharge occurred with difficulty. This was because the graphene surface had hydroxyl, carboxyl, and other functional groups, which was negative charged, making it easy to absorb positive ions . The positive corona discharge current was about two orders of magnitude lower than the negative corona discharge current.…”
Section: Resultsmentioning
confidence: 99%
“…They are good candidates for developing stable atmospheric corona discharge. Boet al used horizontally suspended CNTs as the discharge electrode, which demonstrated that the corona discharge could operate at a much lower voltage. In their subsequent research, vertically oriented graphene was grown on metallic wires for greener corona discharges.…”
Section: Introductionmentioning
confidence: 99%
“…18 Three successive air ionization I-V curves measured from Pt/Si hybrid nanoneedle array gas sensing device, where the repeatability is confirmed by variation of less than 0.…”
mentioning
confidence: 89%
“…One-dimensional nanomaterials (ODNM), in particular, such as carbon nanotube, zinc oxide nanowire or silicon nanowhisker, allow the extensively application as the ideal field ionization devices [11][12][13][14]. In this case, when the applied voltage is raised up to a certain value, the ambient gas will generate conductive plasma to bridge the tips of ODNM and counter-electrode [11,[15][16][17][18][19]. Therefore, a steep increment of ion current can be detected immediately in the measurement circuit.…”
Section: Nanostructure Array: Overview Of Gas Sensingmentioning
confidence: 99%
“…Nanoscience and nanotechnology offer new opportunities for making superior materials for use in a wide range of applications important in industry, energy and health. [1][2][3][4][5][6][7] Because of their use, we can expect that these manufactured materials have the potential to get into the environment sometime during production, distribution, use or disposal. 8 Thus, there are many questions as to the EHS of nanomaterials.…”
Section: Introductionmentioning
confidence: 99%